(untitled) (Ibrahim Cardiac Medical Journal, 2022)
Background & objective: Pregnant women with a previous caesarian section may be offered either vaginal birth or elective repeat caesarian section (ERCS). Detailed antenatal counseling and methodical intrapartum management of women are the key factors for success of planned vaginal birth after caesarean (VBAC). The present study was undertaken to determine the incidence of successful vaginal birth and the maternal and perinatal complications in patients undergoing planned vaginal birth after one previous caesarean section. Methods: This prospective observational study was carried out in the Department of Obstetrics and Gynaecology, Sir Salimullah Medical College & Mitford Hospital (SSMC & MH), Dhaka over a period of one year between January to December 2016. A total of 96 term pregnant women, aged 20 – 35 years, having previous experience of one lower uterine caesarean section with spontaneous onset of labour, vertex presentation of the fetus and adequate pelvis were consecutively included in the study. The main primary outcome variable was fate of trial VBAC (successful vaginal delivery either spontaneous or assisted or ERCS). The secondary outcome variables were maternal and perinatal complications (morbidity and mortality). Result: Over 55% of the women under trial VBAC were 25 – 30 years old with mean age of the women being 26.8 ± 3.7 years. Nearly three-fifths (58.3%) of the women were of normal BMI, 40.6% were overweight. None of the women was obese. Only 15% women had gestational age 40 weeks. The mean interval between the current and the previous births was almost 3 years. In terms of primary outcome, over 60% of the planed VBAC were successfully delivered (52.2% spontaneously and 9.3% with the aid of forceps and vacuum extraction). While maternal complications were uterine rupture (6.2%), hysterectomy (6.2%) and haemorrhage needing transfusion (14.6%), neonatal complications were respiratory distress syndrome (17.7%), perinatal death (10.4%), hypoxic ischemic encephalopathy (4.2%) and sepsis (8.3%). Conclusion: The study concluded that planned VBAC is appropriate for majority of women with a singleton pregnancy of cephalic presentation who have had a single previous lower segment caesarean section (LSCS). However, as the maternal complications (like hysterectomy, haemorrhage etc.) and the perinatal complications including death were much high, utmost caution is advised in selecting the right candidate for VBAC so that the incidence of successful VB could be maximized and complications minimized. Ibrahim Card Med J 2021; 11 (1): 54-61